Language use and gender representation in children’s picture books by Malaysian authors / Nur Amira Pang Abdullah - Nur Amira Pang, Abdullah (2015)
This study attempts to look at the use of language and the portrayal of gender in children’s picture books by Malaysian authors. Reading, being one of the activities frequently done by children, plays an important role as a source of appropriate attitudes and values. Hence, reading materials such as children’s picture books provide then with exposure on gender perception as well as their culture. Reading materials such as picture books may provide inputs on constructing their own gender identity. However, recent research show that gender bias and sexism do exist in educational materials (Bahiyah et al., 2008; Yasin et al., 2012). Hence, this aims to investigate whether elements of gender bias and sexism are found in three selected children’s picture books from 2012’s 50 Best Malaysian Titles for International Rights and in particular written by Malaysian authors. For this study, qualitative approach was adopted and a discourse analysis of the corpus was conducted to identify the linguistic portrayal and gender representation of characters in these three children’s picture books. Apart from the language, the characters were analysed on their portrayal in social roles, occupations, and activities. Using Weitzman et al. (1972) as focus, the illustrations were analysed to identify the appearance of characters, based on gender types, gender-oriented activities and setting of characters. The findings reveal that more males rather than female characters tend to be projected with gender biasness through social roles, occupations and activities. As for the use of visual components, the early picture book portrayed more male over female in outdoor and adventure activities. Male characters are found to be assigned with wider range of activities. The study hopes that the findings would be useful for authors of children’s picture books and parents as well as teachers in the selection of reading materials for young readers.